2019
DOI: 10.1038/s41388-019-0900-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear KIT induces a NFKBIB-RELA-KIT autoregulatory loop in imatinib-resistant gastrointestinal stromal tumors

Abstract: Gastrointestinal stromal tumors (GISTs) are frequently driven by auto-activated, mutant KIT and have durable response to KIT tyrosine kinase inhibitor. However, acquired resistance is an increasing clinical issue in GIST patients receiving front-line imatinib therapy. Our previous studies showed the colocalization of KIT with DAPI-stained nuclei in GIST cells without knowing the role of nuclear KIT in GIST tumorigenesis. In this article, we first identified the binding of nuclear KIT to the promoter of NFKB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
(49 reference statements)
0
6
0
6
Order By: Relevance
“…Cell component separation and immunofluorescence stains demonstrated that AXL and p53 have nuclear colocalization ( Figure 4 A,B). Various studies have shown that nuclear translocation of RTKs (full-length or truncated) by c-secretase cleavage of the full-length receptor, shedding, alternative splicing, or alternative translation initiation, including EGFR, ERBB2, FGFR1, KIT, and AXL, regulates transcription [ 32 , 33 , 34 , 35 , 36 , 37 ]. A recent report found that AXL, but not the other two members of the same family MERTK or TYRO3, is cleaved by α- and γ-secretases in cancer cell lines to generate an AXL intracellular isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Cell component separation and immunofluorescence stains demonstrated that AXL and p53 have nuclear colocalization ( Figure 4 A,B). Various studies have shown that nuclear translocation of RTKs (full-length or truncated) by c-secretase cleavage of the full-length receptor, shedding, alternative splicing, or alternative translation initiation, including EGFR, ERBB2, FGFR1, KIT, and AXL, regulates transcription [ 32 , 33 , 34 , 35 , 36 , 37 ]. A recent report found that AXL, but not the other two members of the same family MERTK or TYRO3, is cleaved by α- and γ-secretases in cancer cell lines to generate an AXL intracellular isoform.…”
Section: Discussionmentioning
confidence: 99%
“…[330][331][332][333] Typical therapeutic blocking agents employed to target KIT include cabozantinib, dovitinib, masitinib, and pazopanib. [334][335][336] At present, two additional clinical trials (NCT01153750, NCT02115542) wait for final results.…”
Section: Kitmentioning
confidence: 99%
“… 10 In many different cancer types, networks of oncogenic master TFs form autoregulatory loops via each other’s SEs. 32 , 33 , 34 , 35 , 36 , 37 Disruption of a single oncogenic master TF is often sufficient to collapse this circuitry, leading to cell death or differentiation. We hypothesize that transcriptional inhibition achieves a therapeutic effect by targeting oncogenic TF autoregulation and inducing selective downregulation of these genes.…”
Section: Introductionmentioning
confidence: 99%